Entrepreneurship barriers and entrepreneurial inclination among Malaysian postgraduate students - Sandhu, Manjit Singh; Sidique, Shaufique Fahmi; Riaz, Shoaib (Emerald Group Publishing, 2011)
Purpose: Postgraduate students who are more mature and have greater job experience are more likely to be inclined towards entrepreneurship. However, postgraduate students face various barriers such as lack of funds, fear of failure and lack of social networking that may hinder their entrepreneurial inclination. The barriers faced by these postgraduate students may also exhibit different dimensions compared with barriers faced by existing entrepreneurs. This study aims to examine the relationship between perceived barriers to entrepreneurship and entrepreneurial inclination. Design/methodology/approach: Based on a survey‐based methodology, data were collected from a sample of 267 postgraduate students from various Malaysian universities. Respondents' perception towards five barriers to entrepreneurship (aversion to risk, fear of failure, lack of resources, lack of social networking, and aversion to stress and hard work) and their entrepreneurial inclination were assessed. Findings: The model R‐squared indicated that 31.5 percent of the variation in the entrepreneurial inclination is explained by the five perceived barriers. The highest ranked barrier to entrepreneurship was lack of social networking followed by lack of resources and aversion to risk. Research limitations/implications: The findings in this study cannot be generalized to non‐student populations since it covers only postgraduate students. The quantitative approach used was unable to uncover in‐depth information on the various barriers. A qualitative approach may be more appropriate to obtain further details. Originality/value: This research provides interesting insights into the entrepreneurship barriers faced by postgraduate students from a developing nation where such research is lacking.